2022
DOI: 10.3390/jcm11164711
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Markers of Bone Turnover, Inflammation and Extracellular Neutrophil Traps on Bone Mass in Haemophilia and the Development of Haemophilic Arthropathy

Abstract: Background: The aim of the study is to evaluate selected biomarkers of bone turnover, inflammation, neutrophil trap and factors predisposing haemophiliacs to bone loss, and to analyse their relationship with clinical features, treatment and complications. Methods: The levels of interleukin 6 (IL-6); citrullinated histone (CH3); osteocalcin (BGLAP); bone alkaline phosphatase (BALP); N-terminal procollagen type I propeptide (P1NP); and C-terminal collagen type I telopeptide (C1CP) were examined in 60 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
0
2
Order By: Relevance
“…In our study, the IL‐6 levels of PwH were higher but not significantly different compared to the controls, while other studies reported higher IL‐6 levels in blood for PwH 8,32 IL‐6 levels were also elevated in synovial fluid of PwH 33 . Like in our study, no significant differences for IL‐6 between PwH and healthy controls were reported by Czajkowska et al 34 . In our study, IL‐6 was also not significantly elevated in HIV‐positive PwH (data not shown) while Böhmert et al 8 .…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In our study, the IL‐6 levels of PwH were higher but not significantly different compared to the controls, while other studies reported higher IL‐6 levels in blood for PwH 8,32 IL‐6 levels were also elevated in synovial fluid of PwH 33 . Like in our study, no significant differences for IL‐6 between PwH and healthy controls were reported by Czajkowska et al 34 . In our study, IL‐6 was also not significantly elevated in HIV‐positive PwH (data not shown) while Böhmert et al 8 .…”
Section: Discussioncontrasting
confidence: 51%
“…In our study, the IL-6 levels of PwH were higher but not significantly different compared to the controls, while other studies reported higher IL-6 levels in blood for PwH 8,32 IL-6 levels were also elevated in synovial fluid of PwH. 33 Like in our study, no significant differ-ences for IL-6 between PwH and healthy controls were reported by Czajkowska et al 34 In our study, IL-6 was also not significantly elevated in HIV-positive PwH (data not shown) while Böhmert et al 8 have shown in subgroup analyses that IL-6 was higher in PwH who were infected with HIV. An increase in IL-6 was also observed in PwH with target joints, which are defined as joints with four haemorrhages within 6 months or joints with a total of 20 haemorrhages.…”
Section: Marker ß-Ngf Pwh ß-Ngf Concontrasting
confidence: 51%